Education and memory. Pedagogy of remembrance and communication design - Daniela Anna Calabi; Beatrice Borghi; Clorinda Sissi Galasso (Agathón)
Memory is rooted into places, and it can be an elective design tool to communicate the evolution of landscapes and to teach the value of memory. The Institute of Higher Education G. Galilei-R. Luxemburg in Milan interpreted the MIUR call for applications ‘Cinema per la scuola – I progetti delle e per le scuole’, proposing memory topics and creating a documentary about the Institute Marchiondi ‘for problematic children’. Communication Design reveals, with educational effectiveness, what lies behind the obsolescent atmosphere of the brutalist ruins of architecture and starts what can be called a ‘pedagogy of remembrance’. The research results in the analysis of the connections between virtual, physical and digital forms of memory, in an interpretative framework that opens to an educational context.